AS DIALÉTICAS DA GLOBALIZAÇÃO: PATRIMÔNIO CULTURAL E TURISMO - Rocha, Ana Rita Pinto (2009)
This study set analysis on the dialectic process between the global and local scales through the relation between the cultural heritage and tourism. Globalization, as long as a dynamics coming from the dialogue between the global and local range arises different interpretative ways, among them the ones that involve cultural heritage and tourism. Subsequently the scales concept and its mutual character it’s used to make explicit that dynamics leaded by the emergence of techniques that limits and are limited by the social environment. At the same time, the nets concept make the foundation for that scenario like connections between the global and the local range that emphasizes its selective mood, because, notwithstanding being global nets, they aren’t universal. Thus, in this work, are discussed two propositions. The first, argues the relevance from the place over the global dynamics in the intellectual authentication for the cultural heritage preservation that express itself as a reference from the place by its social and historical relevance. In this circumstance are found the grounds against the wicked globalization where the capital and information reigns, arising the place’s defensiveness. The second, where the cultural heritage is set on analysis as the basis for tourism that, under the capitalist point of view, determines the logical knowledge of competitiveness between the places, where each place make use of its best goodness and put it at disposal for consumption (localization, landscape, culture) aiming to get ant stay in the global dynamics. Departing from this two propositions, this study analyses the connections and oppositions between them, no matter if to discuss the global changes or to argue in favor to the local authenticity.